Recent Advances in Nanostructured Polymer Composites for Biomedical Applications - Silva, Andre D.R.; Stocco, Thiago D.; Granato, Alessandro E.C.; Harb, Samarah V. [UNESP]; Afewerki, Samson; Bassous, Nicole J.; Hammer, Peter [UNESP]; Webster, Thomas J.; Marciano, Fernanda Roberta; Lobo, Anderson O. (Elsevier, 2019)
The use of nanostructured polymer composites has surged to the forefront as a promising class of hybrid materials to design biomimetic structures for biomedical applications. The association of two or more classes of nanomaterials not only improves the intrinsic properties of composites, but also presents structural and chemical similarity to organic and inorganic parts of our body. A plethora of chemistries, compositions, and nanofillers have been extensively used for biomedical applications, especially for tissue engineering purposes. The great challenge of nanostructured polymer composites is to mimic (chemically and structurally) the extracellular matrices from different parts of the human body to promote tissue regeneration. Herein, we discuss recent efforts and key research challenges regarding natural, synthetic, and hybrid polymers both with and without organic and inorganic fillers employed for biomedical applications. An overview of three-dimensional bioprinting using nanocomposite hydrogels is also presented. We hope that the final comments and future directions presented here will pave the way for designing and conducting innovative research within the field and by that extend the thematic and fundamental understanding.
Keywords: hydrogel; nanocomposites; Nanotechnology; polymers; scaffold